Features of pregnancy course in women with chemoresistant tuberculosis (a literature review) - O. M. Raznatovska; O. S. Shalmin (Zaporožskij Medicinskij Žurnal)
Tuberculosis is a global cause of morbidity among women of reproductive age, constituting a serious maternal and perinatal risk in both developed and developing countries. Tuberculosis is the third highest cause of death in women of reproductive age. At the same time, the frequency of diagnosing a specific process in pregnant women and pregnancy in women with tuberculosis is almost the same. Today, against this background, the treatment of chemoresistant tuberculosis (CR-TB) in pregnant women remains controversial.